Economic burden of colorectal and breast cancers attributable to lack of physical activity in Brazil - Leandro F. M. Rezende; Gerson Ferrari; Luciana Ribeiro Bahia; Roger Dos Santos Rosa; Michelle Quarti Machado da Rosa; Romulo Cristovão de Souza; Dong Hoon Lee; Edward Giovannucci; José Eluf-Neto (BMC, 2021)
Abstract Background The increasing number of cancer patients has an escalating economic impact to public health systems (approximately, International dollars- Int$ 60 billion annually in Brazil). Physical activity is widely recognized as one important modifiable risk factor for cancer. Herein, we estimated the economic costs of colon and post-menopausal breast cancers in the Brazilian Unified Health System (SUS) attributable to lack of physical activity. Methods Population attributable fractions were calculated using prevalence data from 57,962 adults who answered a physical activity questionnaire in the Brazilian National Health Survey, and relative risks of colon and breast cancer from a meta-analysis. Annual costs (1 Int$ = 2.1 reais) with hospitalization, chemotherapy and radiotherapy were obtained from the Hospital and Ambulatory Information Systems of the Brazilian SUS. Two counterfactual scenarios were considered: theoretical minimum risk exposure level (≥8000 MET-min/week) and physical activity guidelines (≥600 MET-min/week). Results Annually, the Brazilian SUS expended Int$ 4.5 billion in direct costs related to cancer treatment, of which Int$ 553 million due to colon and breast cancers. Direct costs related to colon and breast cancers attributable to lack of physical activity were Int$ 23.4 million and Int$ 26.9 million, respectively. Achieving at least the physical activity guidelines would save Int$ 10.3 mi (colon, Int$ 6.4 mi; breast, Int$ 3.9 mi). Conclusions Lack of physical activity accounts for Int$ 50.3 million annually in direct costs related to colon and post-menopausal breast cancers. Population-wide interventions aiming to promote physical activity are needed to reduce the economic burden of cancer in Brazil.